(untitled) (Economic and Political Thought, 2014)
Economy for the common good means an absolute paradigm shift, thus the way of thinking of most scientists about the economy and management, especially its superior objective that determines the selection of management tools. The implementation of the economy for the common good is supported by the Constitution of the Republic of Poland, the first sentence of which provides that “The Republic of Poland shall be the common good of all its citizens.” The basis for the new paradigm of management – the economy for common good – also seems to be prepared: starting with the idea of sustainable development showing that GDP is not the only thing that counts, through the exposure of the role of social capital in the development of economies and communities, to the indication of micro-economization stimulated by greed amongst the sources of the financial crisis at the turn of the 21st century decades and others. However, as the paradigm shift is first of all a change in itself and as such it is subject to specific rules and procedures, the necessary conditions for its existence are agents of change. Generation Y’s authorisation to become an agent of change is its representatives’ community-oriented attitude. On the other hand, the nature of activeness they demonstrate (in Poland and in the world) indicates a positive mode of the paradigm shift through dissemination of ‘good patterns’ of particular communities’/societies’ activities.